Organization Management Influencing Employee Engagement in the Hotel Industry in Henan, China - Song, Sun; Tirathanachaiyakun , Kanyarat (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This study examines the impact of Organization Management on employee engagement in the hotel industry in Henan, China. With the rapid growth of the hospitality sector and increasing reliance on digital transformation, employee engagement has become a critical factor in ensuring service quality, operational efficiency, and business sustainability. The research analyzes the influence of personal factors such as age, gender, and marital status on employee engagement and evaluates how Organization Management, including planning, organizing, leading, and controlling, contribute to workforce motivation and satisfaction. The study employs a quantitative research approach, utilizing a structured questionnaire distributed to 384 hotel employees in managerial positions. Data analysis, including t-tests, ANOVA, and multiple regression, reveals that while gender and marital status do not significantly impact engagement levels, age differences are a determining factor, with younger employees reporting lower engagement. Furthermore, Organization Management play a significant role in employee engagement, with leadership having the strongest influence. Based on these findings, the study recommends enhancing leadership development programs, implementing employee engagement initiatives, improving work environments, leveraging data-driven HR strategies, and investing in technology and training. These measures are expected to improve employee satisfaction, reduce turnover rates, and enhance customer service, ultimately strengthening the competitive position of hotels in Henan.